Naturally Occurring Antimicrobials in Food - Sofos, John N.; Beuchat, Larry R.; Davidson, P. Michael; Johnson, Eric A. (Council for Agricultural Science and Technology (CAST), 1998)
Many biologically derived substances exhibit antimicrobial properties in the foods in which they normally are found or may be developed for commercial use as additives to other foods requiring preservation.
Keywords: Antimicrobials; Properties; Biologically Derived